2019
DOI: 10.1142/s021988781950138x
|View full text |Cite
|
Sign up to set email alerts
|

Stringy dyonic solutions and clifford structures

Abstract: Using the toroidal compactification of string theory on n-dimensional tori, T n , we investigate dyonic objects in arbitrary dimensions. First, we present a class of dyonic black solutions formed by two different D-branes using a correspondence between toroidal cycles and objects possessing both magnetic and electric charges, belonging to U(1) 2 n−1 e ×U(1) 2 n−1 m dyonic gauge symmetry. This symmetry could be associated with electrically charged magnetic monopole solutions in stringy model buildings of the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…It is known that in higher dimensions many physical quantities are reinterpreted from the usual four-dimensional spacetime viewpoint as various faces of possible one quantity. In particular, it has been shown that the single electric and magnetic charges in ten dimensions could be viewed from the 4-dimensional non-compact spacetime standpoint as dyonic charges, being particles carrying simultaneous existence of the electric and the magnetic charges [6]. A dyon with a zero electric charge is usually referred to as a magnetic monopole [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in higher dimensions many physical quantities are reinterpreted from the usual four-dimensional spacetime viewpoint as various faces of possible one quantity. In particular, it has been shown that the single electric and magnetic charges in ten dimensions could be viewed from the 4-dimensional non-compact spacetime standpoint as dyonic charges, being particles carrying simultaneous existence of the electric and the magnetic charges [6]. A dyon with a zero electric charge is usually referred to as a magnetic monopole [7,8].…”
Section: Introductionmentioning
confidence: 99%